Using technology-based activities to improve student engagementhnology-based activities to improve student engagement - Tôn, Thiết (Tạp chí Khoa học HUFLIT, 2024)
This paper explores how using technology-based activities can make students more interested and involved in school. It starts by discussing why it’s important for students to be engaged in their learning. Then, it looks at what students think about engagement and their perspectives. The paper also reviews researches on how technology can help improve student engagement. It shows how technology can change the way teachers teach and how students learn. Furthermore, the paper suggests specific activities that teachers can employ with technology to increase student engagement, fostering exploration, creativity, and collaboration among students.